Caracterização genotípica do Vírus Varicela-Zoster em casos de varicela e Herpes zoster em Belém-Pará, Brasil - COSTA, Marcos Rogério Menezes da (Universidade Federal do Pará, 2017)
Varicella zoster virus (VZV) can cause chickenpox during primary infection, subsequently establishing a latent infection. In case of reactivation of the virus, the herpes zoster may occur. Analysis of the presence of IgG and IgM is critical to determine the prevalence of this virus in the Metropolitan Region of Belém. The study of specific nucleotide polymorphisms is used to define the genotypes of VZV. Analysis of ORFs 22, 38 and 54 identified genotypes of VZV according to the classification established in conference July 25, 2008 in Whitechapel, London / UK, where the strains of VZV detected and characterized by sequencing of SNPs were grouped into classes 1 through 5. To evaluate the prevalence of antibodies and describe the circulating genotypes was the aim of this study. The frequency of IgM and IgG antibodies in cases of chickenpox was 68.2% and 48.2%, respectively. Cases of herpes zoster showed prevalence of anti-VZV IgG and IgM of 87.5% and 12.5%, respectively. The genotypes 1 or 3 and 5 were present in 13 samples sequenced, and the European strain (class 1 or 3) was found in samples from all the cities studied. The identification of strains circulating VZV is extremely important because of the association of specific genotypes with clinical harshest and to assess the implementation of the vaccine in the National Immunization Program.